PP.29.18: REACHING THE TARGET IN A REAL LIFE SETTING. (June 2015) - Destro, M.; Dognini, G.P.; Cagnoni, F.; Pozzi, A.; Galimberti, V.C.; Cavalleri, C.; Panza, S.
Abstract : Objective: Hypertension (HT) represents the most important cardiovascular (CV) risk factor, but the target blood pressure is hardly reached in the majority of patients (pts) and data deriving from outpatient setting are often lacking. This work was conducted during public events (i.e. world hypertension day) in order to assess the prevalence of HT and determine the number of pts reaching the target blood pressure(BP). Design and method: Each participating subject, after signing an informed consent, was asked to fulfil a questionnaire investigating CV risk factors and antihypertensive therapies. BP measurement was performed according to the ESH/ESC guidelines. A brief counselling was finally offered and brochures dealing with HT prevention were provided. Results: Between May 2011 and May 2014, during public events, 1540 subjects were evaluated (mean age = 58y, median = 60y, range = 12-102y, M = 696, F = 845, M/F = 0.82). Among them, 650(=42%) declared to suffer from HT. After measurement, the target BP < 140/90mmHg was observed in 408/650(=target pts, TPts = 63%), non-target pts (NTPts) being 242. A comparison between TPts and NTPts documented a significant association between female sex and BP control (p = 0.0018). On the contrary, no significant differences were observed when considering type and number of CV risk factors, and also when evaluating the number of antyhypertensives taken by each patient, even though BP control rate increased according to the number of antihypertensives taken (64% versus 82% in those taking 1 versus = or > 4drugs). Moreover, among pts taking one only drug, the most represented classes were ACEI(=28%), ARB(=27%), BB(=21%), CCB(=15%), diuretics(=7%), alfa-blockers(=2%) but again the class did not significantly influence BP control rate. Conclusions: Despite the possible bias, our data provide a picture of BP control out of medical setting. While female sex is related to a better BP control, CV risk factors and antihypertensive therapies are not, maybe due to the sample number, thus deserving a better evaluation in future surveys. Importantly, BP control rate in everyday life resulted rather close to the goal of 70% advocated by the Italian Society of Hypertension (SIIA) within 2015.